The Implementation of Paulo Freire Liberation Education and Songwriting Learning in PKBM Omah Dongeng Marwah Kudus - Munkhakim, M. Ali; Sunarto, Sunarto; Syah Sinaga, Syahrul (Catharsis, 2021)
The domination process in education often positions educators as the subject and learners as an object. It means that it negates the active awareness of the learners. In addition, the raising of political policies that are rooted in the positivism philosophy causes the education praxis is only oriented on the intellectual intelligence development of the learners, and it ignores the learners' existence as an individual who has another potential, such as emotional, social, and spiritual dimensions. Therefore, the approach of liberation education proposed by Paulo Freire becomes a relevant attractiveness to be implemented in education as education is a liberation and independence process for humans' awareness to determine their intention towards the world reality, particularly on the art learning aspects. It is supported as art learning needs the liberating education through the problem-solving approach and action and reflection implemented through praxis, namely the unity of intention, words, and works during the songwriting learning in PKNM Omah Dongeng Marwah (ODM) Kudus. This research used the qualitative method with a case study approach. The data collections techniques used in-depth interviews, direct observations, and document studies. The result of the research shows that the music learning model in PKBM-ODM runs freely, which means that the facilitators trust the learners to make their curriculum achievement. Then, the workshop presentation is dialogic learning done by the learners and the facilitators to find solutions regarding the problems they face related to songwriting learning. The last activity discussed is the workshop of hearing to do critical reflection for the learners and facilitators for always being creative and critical individuals.